Better understanding of homologous recombination through a 12‐week laboratory course for undergraduates majoring in biotechnology. Issue 4 (17th March 2017) - Li, Ming; Shen, Xiaodong; Zhao, Yan; Hu, Xiaomei; Hu, Fuquan; Rao, Xiancai
Abstract: Homologous recombination, a central concept in biology, is defined as the exchange of DNA strands between two similar or identical nucleotide sequences. Unfortunately, undergraduate students majoring in biotechnology often experience difficulties in understanding the molecular basis of homologous recombination. In this study, we developed and implemented a 12‐week laboratory course for biotechnology undergraduates in which gene targeting in Streptococcus suis was used to facilitate their understanding of the basic concept and process of homologous recombination. Students worked in teams of two to select a gene of interest to create a knockout mutant using methods that relied on homologous recombination. By integrating abstract knowledge and practice in the process of scientific research, students gained hands‐on experience in molecular biology techniques while learning about the principle and process of homologous recombination. The learning outcomes and survey‐based assessment demonstrated that students substantially enhanced their understanding of how homologous recombination could be used to study gene function. Overall, the course was very effective for helping biotechnology undergraduates learn the theory and application of homologous recombination, while also yielding positive effects in developing confidence and scientific skills for future work in research. © 2017 by The International Union of Biochemistry and Molecular Biology, 45(4):329–335, 2017.